SCLC-J1, a novel small cell lung cancer cell line - Kazuo Ohara (Biochemistry and Biophysics Reports, 2021)
Small cell lung cancer (SCLC) is a type of high-grade neuroendocrine carcinoma. It initially responds to chemotherapy but rapidly becomes chemoresistant and it is highly proliferative. The prognosis in SCLC is poor. We have established a novel SCLC cell line, SCLC-J1, from a malignant pleural effusion in a patient with advanced SCLC. SCLC-J1 cells express ganglioside GD2, CD276, and Delta-like protein 3. RB1 is lost.These features of the new SCLC cell line may be useful in understanding the cellular and molecular biology of SCLC and in designing better treatment.